Interactive behaviors between mothers and their infants at risk for hearing loss - Mariana de Freitas Pereira Pederro; Olga Maria Piazentin Rolim Rodrigues (Estudos de Psicologia (Campinas))
Abstract Objective In the present study, we intended to describe and compare the interaction between mothers and infants at risk for hearing loss (Group 1) and mothers and infants who could hear (Group 2). Method A total of 25 dyads participated in each group and were filmed while free playing. The films were examined using the observation adapted protocol Mother-Child Interaction Coding System, for later comparison. Positive interactive behaviors were significantly more frequent among infants in Group 2. Results Infants in Group 1 showed more non-interactive behaviors than the other group. Mothers in Group 2 showed more positive sensitive and less non-responsive behaviors than mothers in Group 1. Conclusion The results show the importance of the infants’ first social relationships for their development process, especially when there is a risk factor involved, pointing to the need of interventions with families as of the diagnosis phase.